Cyclopropenylgold(I) complexes as aurated carbenoids or quasi-carbenes - Mulks, Florian; Antoni, Patrick W.; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2018)
Highly strained hydrocarbons have always been a research target of high interest. Due to their untypical electronic structure, they show interesting reactivity patterns and can easily be activated by π-coordination to or insertion reactions with metal complexes. Herein we report the synthesis of a range of 3,3-disubstituted cyclopropenylgold(I) complexes. The synthesis of such compounds with a metal, which usually easily activate cyclopropenes is a double-edged sword. We found σ-bound vinylic gold to generally have a strong stabilizing effect in terms of ring strain. The complexes show a strong distortion, preactivating the cyclopropenyls towards the ring-opening mode which thermally generates 1-aurated vinylcarbenes which is reflected by a much faster conversion (Ea of 10 kcal/mol instead of 40 kcal/mol, the reaction proceeds at temperatures as low as −20 °C instead of 200 °C reported in the literature). In 3-phenyl-cyclopropenyl complexes, these could be trapped intramolecularly to give indenylgold(I) complexes. The properties of these highly strained complexes were investigated, utilizing a range of analytical and experimental procedures and Kohn-Sham density functional theoretic methods.
Published online: March 9, 2018
Gesehen am 28.06.2018